TINJAUAN PROSEDUR REKRUTMEN TENAGA KERJA STUDI KASUS BANK BTPN KANTOR CABANG PALEMBANG - Windarti, Gusti Ayu Oka; Anugrah, Bella Meidika (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
The author chose the Palembang branch bank BTPN as a place for data collection on the grounds that currently the banking world has its own attraction to be studied and understood because banks play an important role in economic growth and development in the world including in Indonesia. The author gained knowledge about the recruitment procedures, the implementation of the selection and placement of employees and the constraints in the recruitment procedure for the case study of the Bank's Palembang branch office. As for one of the obstacles in the recruitment procedure of labor such as the incompatibility of the job position given and the applicant, it is better for the BTPN Palembang branch office before assigning tasks and work to workers who pass the selection must be based on the specified job / position specifications, namely position the employee according to the job position being applied for, the skill level and the educational background of the employee. So this can help employees in completing their tasks and responsibilities as well as the achievement of the smooth activities and objectives of the company.